Experimental study on electronic expansion valve failure of a R290 room air conditioner during heating-defrosting process. (25th December 2019) - Du, Yanjun; Wu, Jianhua; Wang, Che; Li, Jinbo
Highlights: It is proved that EEV failure was "oil blockage" at EEV in a R290 RAC. Reasons for oil blockage was low temperature and much oil distributed at after-EEV. During defrost, oil was largely discharged into heat exchangers from compressor. The outdoor heat exchanger lacked refrigerant in start-up of the re-heating mode. Abstract: As an alternative refrigerant for HCFCs, R290 has been gradually applied in commercial refrigerators and humidifiers because of its excellent environmental and thermodynamic properties. The application of R290 in room air conditioner (RAC) is still in the stage of promotion. Abnormal failure of throttle component in heating and defrosting process frequently occurred during developments of R290 RACs. In this paper, the mechanism of abnormal failure of electronic expansion valve (EEV) of a R290 RAC during heating-defrosting process was experimentally investigated in enthalpy-difference laboratory. The compressor and system pipeline were visualized and a viscometer was performed to measure the variation of viscosity in oil sump. The experimental results showed that the EEV failure in the startup stage of heating process, was caused by oil blockage. The oil blockage was mainly caused by much more oil and lower temperature at after-throttling during defrosting and heating-defrosting mode conversion process. The results and analysis of this research can provide an effective guidance for alleviating and eliminating the throttle component failure and improving the reliability of R290 RACs.